Effectiveness of the Social Media of the Department of Communication and Informatics in Providing Information and Education to the Community in Ciamis Regency - Yulia Citra Rahayu; Arie Budiawan; Rindu Garvera (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study aims to determine the effectiveness of social media used by the Ciamis Regency Communication and Informatics Office (Diskominfo) in conveying information and education to the public. The media analyzed included the Hello Ciamis application, Instagram, Facebook, the website, and Twitter. The method used was descriptive qualitative through field and library studies, as well as data collection techniques such as observation, interviews, and documentation. The effectiveness analysis refers to Campbell's five indicators: program success, target success, program satisfaction, input-output level, and achievement of overall objectives. The results of the study indicate that the effectiveness of Diskominfo's use of social media is not optimal. The main obstacles include a lack of socialization, low community participation, limited internet network, low digital literacy, and a lack of utilization of interactive features. Nevertheless, several information and education programs have successfully reached the public and generated satisfaction. Efforts undertaken by the Communications and Informatics Office (Diskominfo) include increasing digital outreach, conducting digital literacy training, strengthening two-way interactions, partnering with community leaders, and adapting content to the community's literacy level. The Office also expanded information reach to remote areas, accelerated information updates, and established a public feedback system. This study recommends strengthening digital communication strategies, increasing the dissemination of the Hello Ciamis application, and utilizing analytical features to evaluate the effectiveness of information delivery to ensure more equitable and targeted distribution.